Clinical decision making and the challenges of responding to mental health needs. (2nd October 2019) - Hutchison, Trudy; Lees, Carolyn; Lotto, Robyn; White, Alison; Harris, Ron
Abstract : The paramedic service responds to emergency calls for a variety of reasons, many relating to mental health concerns. This qualitative study aims to explore the views and experiences of student paramedics in relation to clinical decision making for mental health calls. Focus groups were used to investigate the participants' perspectives. Thematic analysis was used to organise data and identify key issues. Findings suggested some disparity between what paramedic students were prepared for and the reality of public need. Clinical decision making in relation to those with mental health problems was significantly influenced by the current provision of mental health services and the lack of mental health-specific education for student paramedics. Current changes to the paramedic programme make this an opportune time for a review of curriculum content.